An urbanizing world - Brockerhoff, Martin (International Food Policy Research Institute, 2000)
...The urban population in the developing world is expected to double to 4 billion by 2025, accounting for about 90 percent of global population growth....Managing the ongoing rapid urban growth in developing countries, and avoiding the bleak vision of the pessimists, is possible only if governments act energetically on a number of different fronts: reducing urban poverty and inequity, helping women achieve their fertility preferences, improving urban infrastructure, removing bias against rural- based agriculture, and building good governance. -- from Text